The role of gamma interferon in infection of susceptible mice with murine coronavirus, MHV-JHM - Smith, Abigail L. (Arch Virol, 1991)
Infection of BALB/c mice with mouse hepatitis virus, strain JHM (MHV-JHM), at any of several intervals relative to ovalbumin (OVA) administration resulted in elevated OVA-specific IgG 2 a titers. Since gamma interferon (IFN) has been implicated as an up-regulator of IgG 2 a production, attempts were made to determine whether levels of this cytokine were modified in sera of infected mice. Serum IFN-γ was not detected, but treatment of MHV-JHM-infected mice with monoclonal anti-IFN-γ antibody resulted in high mortality with decreased survival times, enhanced virus titers in liver and spleen, and more severe virus-associated pathology, compared to mock-treated, infected mice. Immunotherapy with recombinant IFN-γ ameliorated disease as reflected by mortality rates and virus titers in target organs.